What Do We Know So Far about Multigenerational Mobility? - Gary Solon (Institute of Labor Economics (IZA), 2017)
Multigenerational mobility refers to the associations in socioeconomic status across three or more generations. This article begins by summarising the longstanding but recently growing empirical literature on multigenerational mobility. It then discusses multiple theoretical interpretations of the empirical patterns, including the one recently proposed in Gregory Clark's book The Son Also Rises.
Keywords: D1; D31; D63; J62; 330; multigenerational mobility